Identification of Fe and Mn Heavy Metal in Stream Sedimentation at Putri Cempo Landfill - Rachmawati, Siti; Kusumaningrum, Lia; Aulia, Ahmad Asfar; Utomo, Alifia Namira; Nabila, Iffah; Kurniasari, Intan Dwi; Nurlita, Siti; Aryanto, Anisa Eka Putri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
The Putri Cempo landfill serves as the final disposal site for organic and inorganic waste. Waste from the landfill can dissolve and settle in river sediments, potentially accumulating heavy metals, such as iron (Fe) and manganese (Mn), which easily bind to organic matter. This study aims to determine the content of Iron (Fe) and Manganese (Mn) in rivers around the Putri Cempo landfill. The concentrations of Fe and Mn weres analyzed using atomic absorption spectrometry (AAS) according to SNI 6989.84:2019, with sediment sampling conducted in rivers around the Putri Cempo landfill. Sediment sampling in these rivers revealed Fe levels of 1519.414245 mg/L and Mn levels of 130.033 mg/L. The analysis indicated that Fe concentrations exceeded the established quality threshold, whereas Mn levels remained below it. Heavy metals like Fe and Mn negatively impact abiotic and biotic environments, including human health and agricultural productivity. Elevated heavy metal levels disrupt ecosystem balance and pose health risks, making their management crucial. Reducing heavy metals in river sediments near the landfill is essential. Remediation efforts using bioremediation and phytoremediation technologies can help mitigate these impacts. Ongoing efforts are necessary to control heavy metal contamination in river sediments, ensuring ecosystem stability and public health.